Sufisme dalam Konteks Modernitas Islam: Adaptasi, Transformasi, dan Relevansi Spiritual Kontemporer - Aslam Habibi (PT. Hasba Edukasi Mandiri, 2026)
This study discusses the position and relevance of Sufism in facing Islamic modernity, which is characterized by urbanization, secularization, globalization, and socio-cultural changes. Modernity is often considered a threat to Sufism because it is perceived as a mystical and pre-modern tradition. However, through a qualitative approach based on literature studies, this study shows that Sufism has not declined but has undergone adaptive transformation. Analysis of classical and contemporary literature and empirical studies reveal that Sufism has adapted through changes in spiritual practices, restructuring of Sufi orders, utilization of digital technology, and involvement in social and political fields. In addition to maintaining its spiritual role, Sufism also contributes to the formation of social ethics, strengthening community solidarity, and responding to the crisis of meaning in modern society. These findings challenge the classical thesis of secularization and affirm that Sufism is a dynamic, adaptive, transnational Islamic tradition that remains relevant in the modern and globalized era.